Getting the balance right between functional and non-functional requirements: the case of requirement specification in IT procurement - Johansson, Björn; Lahtinen, Markus (International Journal of Information Systems and Project Management, 2022)
IT procurement represents a business process of high importance, including the ability to articulate requirements that the procurement deals with. Furthermore, specifying requirements is of importance for both procurer and potential supplier, as it functions as central contractual element between the two. The purpose of this article is two-fold: (i) to show how established terminology for requirement specification is represented in current call for bids for the procurement of IT; and (ii) to introduce an organizing framework that may assist procurers in actively addressing functional requirements and business requirements. Ten “call for bids” were examined from a Swedish national procurement database. From the analysis of the bids, it can be concluded that: (i) the call for bids displays a high degree of precision regarding hardware aspects, but less precision regarding software; (ii) supplier experience and competence is stressed, but rarely elaborated on in detail; and (iii) call for bids vagueness may be used as a lock-in opportunity for suppliers. From the discussion on this, a tentative procurement framework is suggested, aiming on increasing the logical transparency for the procurement of IT.